2019
DOI: 10.1186/s12870-019-1874-z
|View full text |Cite
|
Sign up to set email alerts
|

Interactional similarities and differences in the protein complex of PCNA and DNA replication factor C between rice and Arabidopsis

Abstract: Background Proliferating cell nuclear antigen (PCNA), a conserved trimeric ring complex, is loaded onto replication fork through a hetero-pentameric AAA+ ATPase complex termed replication factor C (RFC) to maintain genome stability. Although architectures of PCNA-RFC complex in yeast have been revealed, the functions of PCNA and protein-protein interactions of PCNA-RFC complex in higher plants are not very clear. Here, essential regions mediating interactions between PCNA and RFC subunits in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…This result reflects that plant metabolism slows down after PCNA silencing, and growth may be blocked or stopped. These results suggest that after PCNA gene silencing, DNA replication is blocked and affects chromatin synthesis, which leads to cycle block and several instances of PCD (Qian et al 2019). The DNA laddering results showed the diffused DNA of plants after PCNA gene silencing (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…This result reflects that plant metabolism slows down after PCNA silencing, and growth may be blocked or stopped. These results suggest that after PCNA gene silencing, DNA replication is blocked and affects chromatin synthesis, which leads to cycle block and several instances of PCD (Qian et al 2019). The DNA laddering results showed the diffused DNA of plants after PCNA gene silencing (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…Previous work indicated OsPCNA and CHR721 showed similar functions in genomic stability and cell cycle regulation [15,25]. However, whether OsPCNA functions in the reproductive development just as CHR721 is not clear so far because no mutant of OsPCNA has been reported.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that the homologous OsPCNA in rice played a role in the form of homotrimers [9]. OsPCNA could interact with several proteins, such as OsFEN1, OsGEN-L, and all OsRFC subunits [9,15,23].…”
Section: Introductionmentioning
confidence: 99%
“…No variation in the PCNA1 mRNA levels in galls suggests that its expression is independent of ABAP1 levels and that minimum concentration might be enough to hold polymerase activity. Also, in plants, PCNA1 and its paralogous PCNA2 are highly conserved genes, with similar sequences, structures, and pattern of protein-protein interaction (Qian et al, 2019), suggesting a redundant function that might overcome some imbalances in their expression as for in galls. PCNA1 is an auxiliary protein of DNA polymerase involved in the control of eukaryotic DNA replication and is the major coordinator of DNA repair at replication forks (Kosugi and Ohashi, 2002;Stevens et al, 2002).…”
Section: Abap1 Might Be Participating In a Mechanism That Coordinates The Balance Of The Mitotic Cycle And Endocycle During Gall Inductiomentioning
confidence: 99%